(untitled) (Research, Society and Development, 2020)
Fresh cream is obtained from the separation of fat from whole milk through mechanical processes. It has a high fat content in its composition, in addition to proteins, carbohydrates and water, so it is a product conducive to the development of deteriorating microorganisms. The present work aimed at analyzing the microbiological quality of artisanal fresh cream produced in the city of Pombal, Paraíba. The samples were acquired in three milk processing units in the city of Pombal. After collection, samples were analyzed at the Laboratory of Food Microbiology and Food Quality, Federal University of Campina Grande, Campus Pombal, Paraíba, with the following microbiological analyzes: Coliforms at 45ºC, positive coagulase staphylococci, molds and yeasts and Salmonellae sp. According to microbiological analyzes, for the parameter thermotolerant coliforms (45 ° C), they presented values above what is allowed by the current legislation, in units 1 and 2, this result can be explained by possible failures in the process of cleaning in the units However, when analyzing the results obtained for coagulase positive staphylococci, Molds and yeasts and Salmonella sp, it is noted that the values are within and / or below what is established by the legislation.